Trauma-informed care implementation in the child- and youth-serving sectors: A scoping review - Lowenthal, Ash (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents)

(untitled) (Canada Research Chair in Interpersonal Traumas and Resilience/Chaire de recherche du Canada sur les traumas interpersonnels et la résilience, 2020)
Objectives: Enthusiasm for trauma-informed care (TIC) in the child-and youth-serving sectors (CYSSs) has been growing dramatically over the last decade. However, TIC implementation activity on the ground has far outpaced research and the landscape of TIC implementation scholarship is not well known. This scoping review aims to explore: 1) the nature of TIC implementation research in the CYSSs; 2) the characteristics of the change initiatives being studied; 3) the types of evidence these studies have generated; and 4) the gaps in the literature. Methods: On August 28, 2019, the EBSCO, Scopus, Web of Science and PsycINFO databases were searched for English-language, peer-reviewed articles that mentioned “trauma-informed” and (“child” or “children” or “adolescent” or “youth”) in the title, abstract or keywords. Articles selected for this review reported on TIC implementation processes in the CYSSs. Fifty-four articles published between 2004 and 2019 met the inclusion criteria and were reviewed in-depth for this scoping review. Results: High variability was found in the characteristics of TIC implementation research and practice. However, promising preliminary evidence is beginning to show that TIC implementation can lead to a reduction in violent practices and incidents and can improve service provider knowledge, attitude, behaviour and practice (KABP). However, research shows that improvements to self-reports of KABP are often modest, not always maintained over time and not easily translated into actual changes in behaviour, practice and organizational climate due to a variety of barriers. Conclusion: In order to address these barriers, the preliminary evidence suggests that TIC implementation requires a comprehensive approach that includes commitment from senior leadership, ongoing support, and collaboration within and between service providing organizations and systems.